How to facilitate a brainstorming session: The effect of idea generation techniques and of group brainstorm after individual brainstorm. Issue 3 (2nd September 2018) - Ritter, Simone M.; Mostert, Nel M.
Abstract: There is a growing recognition that creativity is a key factor to an organization's innovation capacity. When facing challenging problems, organizations tend to rely on facilitated idea generation sessions. During these sessions, people are progressively applying different creativity techniques to generate creative solutions. The aim of the current paper was to examin the effect of four idea generation techniques—Silence, Evolution, Random Connections, and Scamper— on the ability to generate creative solutions, and to shed light on the question whether the idea-generation techniques built on each other. The number of solutions generated did not differ between techniques, suggesting that ideation does not get exhausted. With regard to idea quality all four techniques brougth about equal levels of originality. A difference was found between the techniques on usefulness and flexibility, technique 'Random connections' outperformed technique 'Evolution'. Moreover, the current paper examined whether idea generation in groups after individual idea generation has any benefit over-and-above generating ideas individually. The number of ideas generated in groups did not increase nor decrease. Importantly, however, overall the originality did significantly increase, suggesting that generating ideas in a group after generating ideas individually has a beneficial effect on the quality of the ideas generated.